Efektivitas Penerapan Media E-Learning Berbasis Open Source Terhadap Kemampuan Problem Solving Matematis Siswa MTs Di Kabupaten Tangerang - Rina Hidayati Pratiwi; Riesto Atantio Fajri; Hasbullah (Jurnal Penelitian Pendidikan IPA, 2025)
Technology-based learning media is an important tool in supporting interactive and adaptive learning processes in the digital era. This study aims to evaluate the effectiveness of open source-based e-learning media "Mathematics Laboratory: SPLDV" in improving students' mathematical problem-solving abilities at MTs Negeri in Tangerang Regency. The media used is designed to facilitate interactive learning of concepts and applications of the Two-Variable Linear Equation System (SPLDV) in everyday life. The method used is a pre-experiment with a one-group pretest-posttest design, where one group of students is given a pretest, then given treatment using e-learning media, and ends with a posttest. The subjects of the study were grade IX students of MTs Negeri in Tangerang Regency. Data were collected through problem-solving ability tests. The results of the analysis show that open source-based e-learning media "Mathematics Laboratory: SPLDV" can improve students' mathematical problem-solving abilities, seen from the N-Gain percentage of pretest and posttest data of 60.815% which is included in the fairly effective category. This study is expected to provide an alternative for educators in integrating learning technology to improve students' problem-solving abilities in mathematics.